Diet intake and caries status among final year students in IIUM Kuantan Campus - Abllah, Zurainie; Faisal, Ghasak Ghazi; azizan, Nur Iradah; ibrahim, kartina (2019)
One of the most significant factors for caries is diet intake.100 final year students IIUM Kuantan Campus was undergone clinical examination and completed self-administered questionnaire. Statistical analysis was done using SPSS version 22. Chi-square test was used. Majority of respondents took 3 to 4 times food intake per day. Almost half of respondents did snacking between meals. Among the respondent, 41% has low, 35% has moderate and 24% has high DMFT score respectively. Majority of the final year students has low DMFT, mild inflammation gingiva, and high plaque score. Lastly, sugary food did have significant effect to the DMFT.